Patna painting - Archer, Mildred (Gurugram (Haryana) Shubhi, 2025)
Patna School of Painting (also Patna Qalaam, or Patna Kalam) is a style of Indian painting which existed in Bihar, India in the 18th and 19th centuries. Patna Qalaam was the world$1 (Bs first independent school of painting which dealt exclusively with the commoner and their lifestyle, which also helped Patna Kalam paintings gain in popularity. The principal centers of this style were in Patna, Danapur and Arrah. The art historian, Mildred Archer said of the Patna school of Painting that: (3z(BIt marks the fusion of Eastern and Western taste which occurred in the nineteenth century and mirrors the interests and artistic fashions of the period. The school is, in fact, a summary of the complicated interplay of European and Indian cultures in the nineteenth century.(3ys
Keywords: Art and Culture; Paintings- Patna Painting-Bihar